A new model for the design of rectangular combined boundary footings with two restricted opposite sides - Luévanos Rojas, Arnulfo (Revista ALCONPAT, 2016)
This paper presents a new model for design of boundary rectangular combined sapatas with two opposite sides constrained taking into account the real soil pressure acting on the contact surface of the sapata to obtain: Moments around of parallel longitudinal axes to axis “Y-Y”; Moments around of parallel transverse axes to axis “X-X”; Unidirectional shear force (bending shear); Bidirectional shear force (punching shear) to the two columns. The real soil pressure is presented in terms of the mechanical elements acting on each column (P, Mx, y My). The mathematical approach suggested in this paper produces results that have a tangible accuracy for find the solution more economical. Key words: design of sapatas; boundary rectangular combined sapatas; moments; unidirectional shear force (bending shear); bidirectional shear force (punching shear).